The South African manufacturing exporter story - Marianne Matthee; Neil Rankin; Tasha Naughtin; Carli Bezuidenhout (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Existing South African work on firm-level data has been limited by access to large datasets that track firms over time. This paper overcomes this by analysing a new dataset of the population of manufacturing firms that are matched to their export transactions. South African firm-level exporting is similar to the stylized facts of firm-level exporting found internationally. Moreover, heterogeneity that exists within exporting is evident. Not only do exporters differ in terms of the amount exported, but also in terms of the number of products and destinations they export too. These in turn are related to firm-level characteristics including productivity.
Keywords: F10; F14; 330; heterogeneous firms; exports; productivity; firm-level data; multi-destination; multi-products